Proceedings of the 2005 ACM Symposium on Solid and Physical Modeling 2005
DOI: 10.1145/1060244.1060275
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking CAD search techniques

Abstract: While benchmark datasets have been proposed for testing computer vision and 3D shape retrieval algorithms, no such datasets have yet been put forward to assess the relevance of these techniques for engineering problems. This paper presents several distinctive benchmark datasets for evaluating techniques for automated classification and retrieval of CAD objects. These datasets include (1) a dataset of CAD primitives (such as those common in constructive solid geometry modeling); (2) two datasets consisting of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Among the commonly used evaluation methods for shape benchmarking are Princeton Shape Benchmark (PSB) [35] and National Design Repository (NDR) belong to Drexel University [36]. In the current project, one of the most extensive dataset for shape benchmarking, Engineering Shape Benchmark (ESB) developed in Purdue University has been applied based on the advantages discussed by Jayanti et al [37] PSB includes 867 models in 3D form in three main so called super-class comprising Flat-Thin wall components (107 models), Rectangular-cubic prism (281 models) and Solids of revolution (479 models).…”
Section: Engineering Shape Benchmark (Esb)mentioning
confidence: 99%
“…Among the commonly used evaluation methods for shape benchmarking are Princeton Shape Benchmark (PSB) [35] and National Design Repository (NDR) belong to Drexel University [36]. In the current project, one of the most extensive dataset for shape benchmarking, Engineering Shape Benchmark (ESB) developed in Purdue University has been applied based on the advantages discussed by Jayanti et al [37] PSB includes 867 models in 3D form in three main so called super-class comprising Flat-Thin wall components (107 models), Rectangular-cubic prism (281 models) and Solids of revolution (479 models).…”
Section: Engineering Shape Benchmark (Esb)mentioning
confidence: 99%
“…Based on benchmark and multimedia retrieval CAD models such as PSB [24], AIM@Shape [25] and [26], KBRE suggests to classify a family of mechanical components. Thus, the classification groups a set of mechanical parts which define a family of mechanical components such as: the piston, the housings, the crankshaft etc.…”
Section: The Family Of Componentmentioning
confidence: 99%
“…The symmetry transform is useful for shape matching. Bespalov et al [24] presented several distinctive benchmark datasets for evaluating techniques for automated classification and retrieval of CAD objects. Laga et al [25] and Liu et al [26] suggested using discrete spherical wavelets or continuous spherical wavelets to analyze the spherical functions defined by the sampling of the distances between surface and the center of mass of an object.…”
Section: Introductionmentioning
confidence: 99%